Protected areas network development in the Kharkiv region: present and perspectives - Vlashchenko, S.; Vorontsova, I. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Irreversible changes in ecosystems caused by human activities were accumulating for a long period and at present have led to a difficult situation, which in Ukraine is determined as a crisis. Of particular importance are the maintenance of the natural course of basic natural processes, the preservation of unique and typical ecosystems, biological diversity. The most effective form of conservation of valuable natural objects is the reservations; and nature conservation is one of the main directions of conservation of the natural environment. Protected areas network of Kharkiv region is about 2.5% of its territory and is second-to-last value among the regions of Ukraine. Having ratified the international conventions, Ukraine has committed itself to increase the share of protected areas. Analysis of the situation prevailing today in the protected areas network development, points to a number of negative factors, which make impossible realization of the obligations made by Ukraine. Main among them are: elimination of the system of state management, a critical decrease in the level of funding, the contradictions in the current legislation. Existing problems relate to current and emerging protected areas.